Redesign Interior Pondok Pesantren Tahfidzul Qur’an Ibadurrohman Tasikmalaya Dengan Pendekatan Behaviour - Nitami Rahayu, Dean; Akhmadi; Firmansyah, Rangga (Telkom University, 2024)
Formal and informal education in Indonesia has a crucial role in increasing and developing human potential as a whole in physical and spiritual terms. One form of religious education that plays an important role in building a generation of Muslims with noble morals is Islamic boarding schools. Tahfidzul Qur'an Ibadurrohman Islamic Boarding School is a modern Islamic educational institution in Tasikmalaya City. However, interior planning has not yet become a top priority, even though interior space planning in the Islamic boarding school area can provide comfort, especially in interactive and collaborative learning activities in order to improve user quality and the character of the space in the Islamic boarding school. This is proven by the lack of a setting system related to space dimensions, density and room atmosphere. Plus the spatial layout is still less effective so that it is less than ideal in organizing the spatial characteristics. Therefore, it is necessary to redesign the interior of the Tahfidzul Qur'an Islamic Boarding School in the city of Tasikmalaya with the application of Dynamic Modern to make the room more attractive and functional so that it can maximize activities and provide comfort for space users, especially in learning activities by providing solutions to existing space problems. The results of this research are interior design suggestions that can help optimize activities in the school environment, especially in learning activities. Keywords: redesign, islamic boarding school, interactive